Long Wars and the Constitution - Stephen M. Griffin (Harvard University Press, 2013)
IN THE AFTERMATH of the terrorist attacks of September 11, 2001, the American constitutional system was shaken by a series of controversies arising out of the aggressive response of the Bush administration. Prominent among these were furious and deeply felt disputes over the use of torture in interrogation, the treatment of detainees, especially at Guantanamo Bay, and domestic surveillance. The Bush administration came under heavy criticism not only for actions initially taken in secret and unauthorized by Congress, but also for the way it led the nation into the authorized war against Iraq in 2003. Many Americans believed that the war had been foisted on the public in a deceptive way without adequate consideration of its costs. As a result of these controversies, President George W. Bush was only the latest in a long line of chief executives accused of acting as an â€œimperialâ€ president. The advent of the Obama administration did not lead to a stilling of the waters. To an extent surprising to his supporters, President Barack Obama did not break decisively with all of the controversial policies of the Bush administration.1 This suggested a factor common to these administrations was at work. The controversies that plagued the Bush administration and the unwillingness of the Obama administration to change those policies were the latest examples of a long chain of constitutional diffi culties connected with the unilateral exercise of presidential power in foreign affairs and, more specifi cally, the use of presidential power to wage war. Controversies over the use of executive power have existed throughout American history. But they took on a completely new dimension T following the enormous expansion in the capacities of government necessary to prevail in World War II and the Cold War. Seen in this light, the deeply problematic aspects of the Bush administrationâ€™s â€œwar on terrorâ€ belong to a family of constitutional crises that include Watergate in the Nixon administration and the Iran-contra affair in the Reagan administration. These crises are part of a pattern of recurrent policy disasters and constitutional problems linked to the war power that run back to the Truman administration and include both covert and overt military operations such as the Bay of Pigs and the Vietnam War